Geometrie urbane - Pavarini, Stefano (2000)
Proyecto para un estacionamiento bajo la Plaza de la reforma en Cosenza por P. Caruso
Keywords: URBANISMO; PLAZAS; COSENZA; ITALIA; CARUSO, PIETRO; ESTACIONAMIENTOS SUBTERRANEOS